0848 HIV Status and Sleep Disturbance in College Students and Relationship with Smoking. (12th April 2019) - Grandner, Michael; Connick, Elizabeth; Patterson, Freda
Abstract: Introduction: Adults living with HIV have greater sleep difficulties and are more likely to smoke cigarettes. Not known is if these associations are present in younger adults, such as college students, and if current smoking exacerbates the sleep difficulties experienced by college students with HIV. Methods: Data were evaluated from the 2011-2014 waves of the National College Health Assessment, an annual survey conducted by the American College Health Association. Health conditions (including HIV positive status) were self-reported. Participants were also asked whether "sleep difficulties" were "traumatic or difficult for you to handle" over the past 12 months. Number of cigarettes per month was self-reported (classified as smoker or non-smoker). N=112, 807, including N=281 HIV positive, provided data. Logistic regression models were adjusted for age, sex, and survey year. Results: HIV positive students were more likely to be smokers (OR=1.74, 95%CI[1.08, 2.81], p=0.023) and were more likely to experience sleep difficulties (OR=2.20, 95%CI[1.69, 2.85], p<0.0005). An HIV-by-smoking interaction was found (p<0.0005). When models were stratified by smoking, the relationship between HIV status and sleep difficulties was seen among non-smokers (OR=2.11), and this relationship was stronger among smokers (OR=2.62). Conclusion: Among college students, HIV positive status is associated with increased sleep difficulties. These problems are worse among smokers. Not only are sleep interventions warranted in this vulnerable group, but smoking cessation efforts could potentially be enhanced by sleep interventions in this group. Support (If Any): R01MD012734 and R01MD011600 and NCAA Innovations Grant